Sistem Informasi Tracer Study Menggunakan Metode FAST - Ilman Kadori; Muhammad Arul Sendri; Bei Harira Irawan (STMIK IKMI Cirebon, 2021)
The output of the success of the education process needs to be traced by tertiary institutions to find out how many graduates are relevant to the work with the field of knowledge they master is through tracer study. The implementation of the Tracer Study on the STMIK MIC Cikarang campus is still done manually, resulting in the campus difficulty reaching more alumni in filling out the questionnaire. Plus, the campus had to go the extra mile in recapitulating the results of the questionnaire. In this study, the FAST (Framework for Application System Technologies) method is used with the aim of designing a Tracer Study information system that can facilitate the management of alumni data and the results of the Tracer Study. By using this method, a system that can manage alumni data can be designed, and can present alumni data reports. And can provide email notifications given to alumni to update their personal data, so that data is up to date. This system can also recap the results of the tracer study questionnaire conducted by alumni, which can then present the report in graphical form